EKSISTENSI TRADISI “MAPPATETTONG BOLA” MASYARAKAT SUKU BUGIS DESA ANABANUA KECAMATAN BARRU KABUPATEN BARRU DALAM PERSPEKTIF HUKUM ISLAM - Muh. Sudirma; Mustaring Mustaring; Rinda Muliati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
This article describes the research on the existence of the “Mappatettong Bola” tradition of the Bugis tribe in Anabanua Village, Barru District, Barru Regency in Islamic Law Perspective. This study uses data collection techniques by making observations, interviews, and documentation. The data that has been obtained from the research results are processed using qualitative descriptive analysis. The results showed that (1) the tradition of